Evaluation of the Efficiency of Sulfur Dioxide Releasing Acetate Cellulose Sheets on the Shelf life of Kiwi Fruits in the Cold Store - Razieh Niazmand; Parvin Sharayei; Moslem Jahani; Elham Azarpazhooh; Mohammad Reza Abdollahi Moghaddam (Pizhūhish va Nuāvarī dar ̒Ulūm va Sanāyi̒-i Ghaz̠āyī, 2023)
The aim of the present study was to evaluate the efficiency of sulfur dioxide release sheets on the basis of acetate cellulose film to control the growth of molds, especially botrytis cinerea, during the storage period of kiwifruit. For this purpose, the storage of kiwifruit inoculated with botrytis cinerea in the presence of one and dual sulfur dioxide releasing sheets (containing 30 and 50% metabisulfit salts, respectively) on the acetate cellulose bed was investigated. After 15 days of storage (9 days in cold store and 7 days in ambient temperature), the least bursting and crushing (4.5%) was obtained in the presence of single-stage sheets that were placed on the surface and bottom of the packages. Also, in the ninth day, mold was not observed in the 60% of packages in the presence of sulfur dioxide releasing sheets. On the 15th day, the amount of total sugar, acidity, firmness, residual sulfur, and soluble solids in packaged kiwis in the presence of two dual releasing sheets placed on the surface and bottom of packages were, respectively, 9.9 g/100 g, 1.09%, 4.75 N, 0.24 mg/g and 12.21%. In general, it can be said that sulfur dioxide releasing sheets have an effective function on cold storage in increasing the shelf life of fruits, especially fruits that are attacked by gray mold.